Structural Response of the Metro Tunnel under Local Dynamic Water Environment in Loess Strata. (11th February 2019) - Qiu, Junling; Qin, Yiwen; Lai, Jinxing; Wang, Ke; Niu, Fangyuan; Wang, Hao; Zhang, Guanglong
Abstract : The reasons, prevention, and control of loess disaster are of great concern in practice. In recent years, Xi'an city, China, has taken the leadership in large-scale construction of subway lines in the loess strata. To study the structural response of the tunnel in loess region under local hydrodynamic environment, an experimental testing in 1g as well as a numerical simulation were performed, in which the achieved results were verified and were found to be in good agreement. Furthermore, the results showed that when the water outlet point is above the lining, the overall stress of the lining is "peanut shell, " as the water pressure of the outlet point decreases, the tensile stress of the top and bottom of the lining increases, while the compressive stress on both sides decreases; the channel form of the flow to the lining changes with the variation of the position of the water outlet point. It is worth mentioning that in the process of water gushing, the closer to the water source, the greater surface subsidence is, and there is a positive correlation between water pressure and surface subsidence. This study is of significant benchmark for the construction, maintenance, and prevention of tunnel in loess strata under the influence of water environment.